1995
DOI: 10.1093/ajcn/61.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue differences in black and white women

Abstract: Fat distribution and metabolic variables were studied in 8 black and 10 white age- and weight-matched obese women undergoing a 6-mo weight-reducing regimen. Fat patterning was determined by using anthropometry and computed tomography to quantitate total, subcutaneous, and visceral adipose tissue (VAT) areas at the L2-L3 and L4-L5 levels of the lumbar spine, before, during, and after a modified fast. Black women had smaller depots of VAT than white women at both the L2-L3 (P = 0.004) and L4-L5 (P = 0.054) sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
161
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(188 citation statements)
references
References 27 publications
24
161
3
Order By: Relevance
“…Unlike the result of this study showing that the odds of hypertension is attributable to racial/ethnic differences in regional fat localizations, some investigators found higher insulin resistance in Black women than White women despite lower abdominal and truncal adiposities. [54][55][56] The observed differences in the association between regional obesity and hypertension in this study compared with others, highlights the need for a universal definition of these obesity phenotypes.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Unlike the result of this study showing that the odds of hypertension is attributable to racial/ethnic differences in regional fat localizations, some investigators found higher insulin resistance in Black women than White women despite lower abdominal and truncal adiposities. [54][55][56] The observed differences in the association between regional obesity and hypertension in this study compared with others, highlights the need for a universal definition of these obesity phenotypes.…”
Section: Discussioncontrasting
confidence: 45%
“…50,51 In populations of obese Pima Indians, abdominal obesity was found to be associated with elevated insulin and glucose concentrations. 52,53 The higher prevalences of abdominal and truncal obesities in Blacks in this study compared with lower values that have been observed by some investigators 54,55 may be attributed to differences the definitions of abdominal and truncal adiposities. Unlike the result of this study showing that the odds of hypertension is attributable to racial/ethnic differences in regional fat localizations, some investigators found higher insulin resistance in Black women than White women despite lower abdominal and truncal adiposities.…”
Section: Discussioncontrasting
confidence: 44%
“…8 The more cardioprotective plasma lipoprotein profile found in abdominally obese black vs white persons was partly explained by a lower visceral AT accumulation and a higher plasma lipoprotein lipase activity in black individuals. 9 Hence, as also shown in the WHO MONICA study, the issue of the sensitivity and specificity of detecting abdominal obesity may be populationspecific.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that women of African descent are more susceptible to central obesity 11,12 , a condition that is strongly associated with chronic non-communicable diseases, such as hypertension 13 .…”
Section: Introductionmentioning
confidence: 99%